2014
DOI: 10.1073/pnas.1408905111
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photophysical studies of self-assembled multicomponent supramolecular coordination prisms bearing porphyrin faces

Abstract: Multicomponent self-assembly, wherein two unique donor precursors are combined with a single metal acceptor instead of the more common two-component assembly, can be achieved by selecting Lewis-basic sites and metal nodes that select for heteroligated coordination spheres. Platinum(II) ions show a thermodynamic preference for mixed pyridyl/carboxylate coordination environments and are thus suitable for such designs. The use of three or more unique building blocks increases the structural complexity of supramol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 70 publications
3
60
0
4
Order By: Relevance
“…The coordination of Cu II onto the bipyridyl group without breaking the molecular framework of the tetrahedral cage indicates the compatibility of different coordination interactions. This is a rare example of modifying a coordination cage at specific binding sites through coordinative interaction …”
Section: Resultsmentioning
confidence: 99%
“…The coordination of Cu II onto the bipyridyl group without breaking the molecular framework of the tetrahedral cage indicates the compatibility of different coordination interactions. This is a rare example of modifying a coordination cage at specific binding sites through coordinative interaction …”
Section: Resultsmentioning
confidence: 99%
“…As one knows, the spontaneous formation of metal–ligand bonds is the basis of a well-established methodology for the construction of supramolecular coordination complexes (SCCs) via coordination-driven self-assembly process. SCCs as another kind of metal–organic complexes encompass discrete systems in which meticulously selected metal centers through self-assembly with ligands containing multiple binding sites oriented with specific angularity to generate a finite supramolecular complex 21 29 . SCCs can employ rigid organic ligands as structural linkers, and these organic linkers can be usually modified with functional groups that can be meticulously chosen not to interfere with self-assembly process.…”
mentioning
confidence: 99%
“…Coordination‐directed self‐assembly has been shown to be an effective way to generate cofacial bisporphyrin boxes or cages . Molecular clips were shown to be effective in constructing boxes and cages . In our previous study, we demonstrated that a large molecular rectangle [Au 4 ( μ ‐PAnP) 2 (4,4′‐bipy) 2 ] 4+ (7.921(3)×16.76(3) Å) can be assembled by combining a gold clip [Au 2 ( μ ‐PAnP)Cl 2 ] (PAnP=9,10‐bis(diphenylphosphino)anthracene, Scheme ) with a 4,4′‐bipyridine (4,4′‐bipy) .…”
Section: Methodsmentioning
confidence: 99%